AS-SUNNAH SEBAGAI SUMBER HUKUM ISLAM DALAM ERA YANG PROBLEMATIK - Laila Lailatul Qodriyyah; Yuhana Rizki Farista; Zulham Maula Farid (Indonesian Journal of Law and Islamic Law (IJLIL), 2021)
As-Sunnah or what we often call Sunnah is the plural form of the word sunan which means "habit" or "to be done". At first glance it is similar to the Hadith, but it is different if the sunnah is everything that is quoted from the Prophet, whether in the form of words, practices, or in the form of provisions, teachings, characteristics, behavior, and life journey before the Prophet was appointed as an apostle. Meanwhile the hadith existed after the prophet was appointed as a messenger. There are two more terms that are similar but different, namely Khabar and Atsar. The function of sunnah in the Koran is ta'qid (as reinforcement), tabyin (as an explanation), and mustaqillah. In addition, the relationship between sunnah and al-Qur'an is like two complementary things between mubayyin and maudhu al bayan, mufashil and maudhu ijmal and between juz'i and kulli.